Cell Surface Receptors A Short Course on Theory and Methods - Limbird, Lee E. (Springer US : Imprint: Springer, 2005)
Cell Surface Receptors: A Short Course on Theory and Methods, 3rd Edition, links theoretical insights into drug-receptor interactions described in mathematical models with the experimental strategies to characterize the biological receptor of interest. The study of receptors has changed considerably over the period of the publication of the three editions of this book. The cloning of several genomes makes it unlikely that preparations of receptors now or in the future will arise from their purification as trace proteins from native tissues, but rather from a myriad of molecular approaches. Nonetheless, understanding the molecular mechanisms and ultimately the in vivo biology of these receptors means that investigators will engage in molecular, cellular and ultimate in vivo strategies. It should be of value to investigators who want to identify, characterize and understand the biology of a receptor of interest. This book is primarily targeted to researchers and graduate students in the fields of molecular pharmacology, receptors, receptor biology, and signal transduction. These courses are variously found in pharmacology, molecular and cell biology, biochemistry and neuroscience. Researchers in the pharmaceutical industry working on bringing new drugs to market will also find this book useful.